Disseminated Histoplasmosis in HIV patients- Case series from a single tertiary care centre in India - Sumit Arora; Kuldeep K Ashta; Syed Asif Hashmi; N Arun; Sharmila Dudani (Wolters Kluwer Medknow Publications, 2022)
Introduction: HIV-positive patients are at risk of developing various opportunistic infections, including disseminated histoplasmosis, the incidence of which is 29% in India. Diagnosis is usually delayed as the clinical manifestations are diverse and mimic other common diseases endemic to this region such as tuberculosis and visceral leishmaniasis. This leads to preventable morbidity and mortality. Materials and Methods: We carried out a retrospective data analysis of 1280 HIV positive patients' who were on treatment at our centre between 2016 and 2020., of which 8 cases of confirmed histoplasmosis were identified. The clinicopathological spectrum and outcomes of these patients were analyzed and presented as a case series. Results: The median age of patients was 39.5 years. In six out of eight patients, disseminated histoplasmosis was the initial presentation of HIV. Fever, weight loss, macular-papular skin lesions, bicytopenia, and respiratory system involvement were the most common clinical manifestations. Pulmonary lesions included patchy areas of consolidation, miliary nodules, and pleural effusion. Gastrointestinal symptoms were uncommon. In six out of eight patients, CD4 count was <50/mm3. The median CD4 count and median HIV RNA at presentation were 21.5 per mm3 (interquartile range [IQR]: 12-54) and 2.98 × 105 copies/ml (IQR: 1.24 × 104-5.33 × 106), respectively. Diagnosis in all cases was made by direct visualization of the fungus on biopsy. Most patients responded to L-amphotericin or itraconazole. Three out of eight patients expired due to septic shock following disseminated disease. Conclusion: A high index of clinical suspicion along with early institution of therapy is essential to reduce mortality.